Prevalence and associated factors for the development of hypothyroidism within one year of radioactive iodine therapy among patients with hyperthyroidism in HUSM. - Sayuti, Suzila Che (2013)
Prevalence and associated factors for the development of hypothyroidism within one year of radioactive iodine therapy among patients with hyperthyroidism in HUSM. Many studies had been done regarding the incidence of hypothyroidism post RAI therapy and the associated factors for its development in patients with hyperthyroidism. However there are limited studies done in our local population and there was no similar study done in HUSM in the past. Knowing the prevalences and associated factors for the development of hypothyroidism post RAI is important to predict the possible outcomes of the patients undergoing this mode of therapy. This study objectives were to determine the prevalence of hypothyroidism post radioactive iodine therapy and to determine the association of age, race, gender, aetiology of hyperthyroidism, dose of radioactive iodine used, presence of autoantibodies and usage of antithyroid drug post RAI with the development of hypothyroidism post RAI therapy. The study was a retrospective study performed from September 2012 to November 2012. The participants were patients with hyperthyroidism who received radioactive iodine therapy in Nuclear Medicine Clinic, HUSM since 2002 till 2011 and continued follow up under Klinik Pakar Perubatan. All the records were reviewed. Patients’ data and results, including age, race, sex, aetiology of hyperthyroidism, presence of autoantibodies, dose of RAI used, usage of antithyroid drug and serial thyroid function test post therapy were included in the analysis. Total of 167 patients screened Total and 137 subjects were enrolled in the study. The prevalence of hypothyroidism within one year of RAI therapy seen was 32.9%. The study showed that, gender and usage of antithyroid drug post RAI were significantly associated with the development of hypothyroidism post RAI therapy (P=0.045 and P <0.001). However, other factors; age, race, dose of RAI and aetiology of hyperthyroidism statistically not significant as associated factors for development of hypothyroidism. Female gender had less chance to develop hypothyroidism compared to male (0.406 ,95%CI 0.181,0.908) and those who on antithyroid drug had less chance to become hypothyroid (0.188, 95%CI 0.081,0.438) post RAI compared to patient who was not on antithyroid drug after RAI therapy. We found that the prevalence of hypothyroidism post RAI therapy within one year post RAI are lower compared with previous studies. High precentage of study subjects remained hyperthyroid Factors such as age, race, aetiology of hyperthyroidism and dose of RAI were not significant as associated factors for the development of hypothyroidism. Female gender and those who on antithyroid drug post RAI had less chance to developed hypothyroid post RAI therapy (OR 0.406 and OR 0.188).